2013
DOI: 10.1002/cbin.10059
|View full text |Cite
|
Sign up to set email alerts
|

Role of altholactone in inducing type II apoptosis signalling pathway and expression of cancer‐related genes in cervical carcinoma HeLa cell line

Abstract: Goniothalamus species (Annonaceae) is a shrub that grows in the rainforest of tropical Asia. Several compounds have been isolated and exhibit the potential use for cancer treatment. In this work, altholactone isolated from Goniothalamus macrophyllus was investigated for its cytotoxicity, apoptosis signalling and the expression of cancer‐related genes in the cervical carcinoma HeLa cells. Cytotoxicity was evaluated by MTT assay. Apoptotic characteristics were evaluated by morphological studies. Caspase‐3 activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(39 reference statements)
2
4
0
Order By: Relevance
“…2). These results demonstrated that altholactone induced growth inhibition of T24 cells similar to the effects on other types of cancer cells including leukemia (10), colorectal (11) and cervical cancer cells (8).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…2). These results demonstrated that altholactone induced growth inhibition of T24 cells similar to the effects on other types of cancer cells including leukemia (10), colorectal (11) and cervical cancer cells (8).…”
Section: Resultssupporting
confidence: 55%
“…1) or goniothalenol belongs to the styryllactone family and is a tetrahydrofurano-2-pyrone. It has been reported to exhibit antitumor activity, including inhibition of Bcl-2 and increased p53 expression in human cervical cancer HeLa cells (8), suppression of cell growth of human lung cancer COR-L23 cells (9), and induction of apoptosis in human HL-60 leukemia cells through oxidative stress (10) and in human colorectal cancer (CRC) cells through caspasedependent and -independent apoptotic pathways (11).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that 5 mM NAC diminished the effect of alhtolactone on DU145 cells and support the notion that alhtolactone induces cytotoxic effects by targeting the ROS metabolism (data not shown). These findings are the parallel with the previous studies in which alhtolactone has been reported as a growth inhibitor of different cancer cell lines such as bladder cancer T24 cells [ 15 ], cervical carcinoma HeLa cells [ 13 ] and human colorectal cancer cells [ 12 ].…”
Section: Resultssupporting
confidence: 90%
“…Zhao and Li [ 15 ] have reported that altholactone exerts its in vitro anticancer action by Akt inhibition. Hence, considering current and previous findings, there is the possibility that altholactone may also act via inhibition of the PI3K-Akt-mTOR pathway that plays a key role in oncogenesis [ 39 , 40 ] and with possibility that altholactone promoted p53 expression, as previously has been reported [ 13 , 41 ], could mediate altholactone-induced anticancer action. Further in vivo or preclinical studies are needed to elucidate the anticancer potential of altholactone in combination or adjuvant therapies for the treatment of cancers.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation